2021
DOI: 10.3390/children8090783
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration Is Associated with Poor Treatment Response in Pediatric Pulmonary Vein Stenosis

Abstract: Intraluminal pulmonary vein stenosis is a disease with significant morbidity and mortality, though recent progress has been made using multimodal therapy with antiproliferative agents. The aim of this study was to evaluate the association between aspiration and poor treatment response in patients with intraluminal pulmonary vein stenosis. A retrospective, single-center cohort analysis was performed of patients treated with a combination of imatinib mesylate and multimodal anatomic relief between March 2009 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Patients who are at risk of a poor outcome include those with a younger age and/or lower weight at presentation, a higher number of affected veins, higher severity of disease in the affected veins, severe secondary PH, presence of RV dysfunction, and aspiration. 13,29,35,[43][44][45][46][47][48] Patients with single-ventricle physiology are particularly vulnerable. Patients who respond to therapy thrive, require fewer and less frequent interventions, have shorter hospital stays following reintervention, and have declining RV pressure.…”
Section: Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…Patients who are at risk of a poor outcome include those with a younger age and/or lower weight at presentation, a higher number of affected veins, higher severity of disease in the affected veins, severe secondary PH, presence of RV dysfunction, and aspiration. 13,29,35,[43][44][45][46][47][48] Patients with single-ventricle physiology are particularly vulnerable. Patients who respond to therapy thrive, require fewer and less frequent interventions, have shorter hospital stays following reintervention, and have declining RV pressure.…”
Section: Surgerymentioning
confidence: 99%
“…Lung disease of any kind, including BPD, interstitial lung disease, malacia, apnea, chronic atelectasis, lower respiratory infections, and aspiration, are associated with PVS. [19][20][21]31,48 Patients with aspiration, in particular, are more likely to have a poor treatment response. 48 It is unclear whether it is the inflammatory process associated with these conditions that is the initial nidus in the lungs that ultimately drives the fibromyxoid proliferation in the veins.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies found that poor outcomes from PVS in children are associated with bilateral pulmonary vein involvement, smaller size and younger age at diagnosis, and underlying concomitant lung disease [9][10][11][12][13][14][15][16]. Among the studies investigating risk factors for poor outcomes in children with PVS, the most recent study, which demonstrated an association between aspiration and poor outcome in pediatric PVS, is receiving special attention because aspiration is a potentially modifiable risk factor [17].…”
Section: Introductionmentioning
confidence: 99%